(SOF XR KAPAXR VXJ \Y[Js - Sartre Jean Paul ((SAuvfplejws)
(SASRXFNFL XRP (B3 (SXROR XJV XULNRDLAV (B"(SEURORL XJV FNFYKFULAV(B". (SSU]XRV XRORV(B: (SJNLMLA XJV NRDLMJV EFYXFURV XRORV(B: (SAPAVXRNJs
(SASRXFNFL XRP (B3 (SXROR XJV XULNRDLAV (B"(SEURORL XJV FNFYKFULAV(B". (SSU]XRV XRORV(B: (SJNLMLA XJV NRDLMJV EFYXFURV XRORV(B: (SAPAVXRNJs